Fuel poverty exposure and drivers: A comparison of vulnerability landscape between Egypt and Jordan - Fateh Belaid (Luxembourg Income Study (LIS), 2020)
This article, using ERF-LIS harmonized microdata, develops an empirical model to investigate the unexplored extent and fuel poverty explanatory factors in Egypt and Jordan. First, we use the "Low income - High Consumption" indicator to measure the fuel poverty extent. Second, we implement a multivariate statistical approach to untangle the fuel poor household profile. Then, to explore the factors driving the risk of falling into fuel poverty situations we use a logistic regression model. This research is an important empirical contribution to the sparse literature of fuel vulnerability in MENA countries. It puts forward an empirical approach, which is helpful in discerning and targeting families most in need of energy and financial related assistance. From policy perspectives, the findings provide promising ways of accounting for the fuel poverty phenomenon as a vector of inequality trends in the MENA region. The main findings of the research point to the crucial instrumental role of economic conditions, reducing inequalities and access to education facilities in attenuating fuel poverty in Egypt and Jordan. Policies that mitigate fuel poverty may thus have direct impacts on both well-being and inequalities reduction.
Keywords: C1; D1; I3; Q4; 330; Fuel poverty; Energy Justice; Inequality; Residential energy consumption